Transforming health markets in Asia and Africa : improving quality and access for the poor - Bloom, Gerald (Abingdon, Oxon : Routledge, 2013)
"Markets for health-related goods and services have spread rapidly in many low and middle-income countries. This has substantially increased the availability of health-related goods and services, but it has created problems with safety, efficacy and cost. Making Health Markets Work addresses the challenge of improving health markets so that they better meet the needs of the poor.This book gathers together for the first time information about these little understood yet pervasive systems and offers evidence-based recommendations for policy-makers and private and public sector health managers. It presents a new way of understanding highly marketized health systems, applies this understanding to an analysis of health markets in countries across Asia and Africa and identifies some of the major new developments for making these markets perform better in meeting the needs of the poor"--Provided by publisher.
Transition in the Indian healthcare market / Barun Kanjilal and Sumit Mazumdar -- Lessons from an intervention programme to make informal health care providers effective in a rural area of Bangladesh / Mohammad Iqbal [and others] -- Drug detailers and the pharmaceutical market in Bangladesh / M. Hafizur Rahman and Smisha Agarwal -- China's rural hospitals in the transition to a market economy : a case study in two peri-urban counties in Guangxi province / Gerald Bloom [and others] -- Informal markets in sexual and reproductive health services and commodities in rural and urban Bangladesh / Hilary Standing, Sabina Faiz Rashid, and Owasim Akram -- Improving the performance of patent medicine vendors in Nigeria / Oladimeji Oladepo and Henry Lucas -- Yes, they can : peer educators for diabetes in Cambodia / Maurits van Pelt [and others] -- Evidence of the effects of market-based innovations and international initiatives to improve the performance of private providers / Claire Champion, Gerald Bloom, David Peters --- A review of ICT innovations by private sector providers in developing countries / Henry lucas -- The economics of social franchising for health in low and middle income countries / David Bishai and Claire Champion -- Conclusions : making health markets work better for poor people / Gerald Bloom [and others].
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Medical care -- Africa; Medical care -- Asia; Health care reform -- Africa; Health care reform -- Asia; Health services accessibility -- Africa; Health services accessibility -- Asia; Electronic books